Keterlibatan dan Kinerja Karyawan dalam Meningkatkan Profitabilitas Perusahaan - Holidin Holidin (Fakultas Ekonomi dan Bisnis, Universitas Islam Raden Rahmat Malang, 2022)
Employees who are engaged, committed, passionate, and passionate about their work exhibit high levels of job involvement. In this article, the literature on employee engagement is reviewed using studies from academic and corporate sources. The definition of employee job engagement, how it is assessed, how often it occurs, the consequences of disengagement, the business benefits associated with positive engagement, and changes that might be made in the workplace to promote engagement are some of the areas of concern. Employers are now aware that they can develop a more effective and productive workforce by concentrating on employee engagement. Without intentional involvement and engagement of the workforce, no improvement initiative launched by management can succeed. The results show that a workplace behavioral health approach that targets supervisory communication, job design, resource support, working conditions, business culture, and leadership style can promote job involvement in increasing the profitability of a company. In a case study of an organization that tracks employee engagement and uses data to improve workplace culture, employee talent and employee performance can increase company profitability so the implications for improving behavioral health offerings and employee assistance providers can be optimized